Stationary Time Statistical Property of Ionospheric Clutter in High-Frequency Surface-Wave Radar. (3rd November 2019) - Shang, Shang; He, Kangning; Wang, Zhaobin; Yang, Xuguang
Abstract : In HFSWR (high-frequency surface-wave radar) system, the detection performance is impacted seriously by ionospheric clutter. Frequency selection is an effective method to avoid the effect of ionospheric clutter. The key to the method is the stationarity of ionospheric clutter over a period of time. This paper mainly researches the stationary time statistical property of the ionospheric clutter. A large number of real data including ionospheric clutter in HFSWR are processed and analyzed. It shows that ionospheric clutter in HFSWR has the characteristics of approximate stationarity within a period of time.